Experimental Analysis of Local and Average Dynamic Longitudinal Engineering Compressive Strains in Ductile Porous Rod After the Taylor Direct Impact Experiment - Marcin SARZYŃSKI (Wojskowa Akademia Techniczna, 2015)
The recent experimental method for determining dynamic longitudinal engineering compressive local strain, εl (x), (x is Lagrangian coordinate) and average one, εa, in a ductile porous rod, plastically deformed by Taylor direct impact experiment (Taylor DIE) is presented in this paper. Analysis of strain distribution, εl (x), along axis of the rod was performed by means of this method. There are two essential singularities in this distribution, namely: the first – the maximum compressive strain, εl max, there is in a near of the striking end rod, but it does not locate on the target face; and the second – at high loading (impact velocity), value of the maximum, εl max, decreases together with increasing of initial rod porosity, inversely than at static loading. The values of the strains εl (x) and εa are limited by the impact velocity U. Influence of the moderate porosity (e.g. for copper – Δsa < 20%) on values of the εl (x) and εa is in the order of several percent and it may be neglected.
Keywords: Metalurgia proszków